Can matter and spirit be mediated through language? Some insights from Johann Georg Hamann - Tönsing, Detlev (HTS teologiese studies, 2012)
The Enlightenment introduced to European philosophy and thought-patterns the strict dichotomy between res extensa and res cogitans; that is, matter and spirit. How to overcome the dichotomy and conceive of the interactions between these planes of reality has since become an overarching issue for philosophers. The theory of evolution, as founded by Charles Darwin, understands human beings, with their ability to think, to have arisen in the evolutionary process. Neuroscience utilises insights from the theory of complex systems to attempt to understand how perception, thought and self-awareness can arise as a consequence of the complex system that is the brain. However, already at the height of the Enlightenment, a contemporary and critic of Immanuel Kant, Johann Georg Hamann, suggested a metaphor for understanding the interrelationship of matter and thought. This metaphor is language. The appropriateness of this metaphor can be seen both in the importance that language abilities play in the evolutionary transition to the human species and in the characteristics of complex adaptive systems.